Masalah Kanker Paru pada Usia Lanjut - Putra, Andika Chandra; Nurwidya, Fariz; Andarini, Sita; Zaini, Jamal; Syahruddin, Elisna; Hudoyo, Ahmad; Jusuf, Anwar (PT. Kalbe Farma Tbk., 2015)
Kanker paru masih menjadi masalah kesehatan yang sulit diatasi bukan saja karena meningkatnya jumlah perokok di Indonesia tetapi juga disebabkan tingginya mortalitas dan morbiditas penderita. Beberapa panduan pengobatan merekomendasikan penanganan multimodalitas. Tatalaksana kanker paru cenderung tidak optimal pada usia lanjut padahal hampir separuh penderita kanker paru berusia di atas 65 tahun. Pasien kanker paru berusia lanjut sering memiliki penyakit komorbid, status tampilan buruk serta risiko toksisitas terapi tinggi. Tulisan ini merupakan tinjauan pustaka tatalaksana kanker paru pada usia lanjut.Lung cancer remains a health problem in Indonesia because of increase of young smokers and its high mortality and morbidity. There is a tendency of inadequate management of lung cancer among elderly patients despite fact that almost half of lung cancer patients aged over 65 years. Lung cancer management is still challenging and need comprehensive approach since older patients are more likely to have decreased functional reserve which limit their ability to undergo surgery or receive chemotherapy. Several guidelines recommended multimodality treatment. Ageing is also associated with increased co-morbid medical conditions that could exacerbate and influence outcome. This article will discuss treatment of lung cancer in elderlies.